Colloidal stability of carbon nanotubes in an aqueous dispersion of phospholipid - Douroumis, Dionysios (Dove Medical Press, 2007)
Within the family of nanomaterials, carbon nanotubes (CNTs) have emerged as a new efficient scaffold for studying molecular interactions at interfaces. Poor dispersability of CNTs in any solvent presents a considerable drawback for the development of novel functional composite structures. Previous studies have demonstrated that the solubility of CNTs can be greatly enhanced by employing appropriate surfactants, some of them being biological molecules. In this work, we study the noncovalent wrapping of lipid chains onto the graphitic surface of single-walled material (SWCNTs) by electron microscopy and Raman spectroscopy. Stable and homogenous aqueous suspensions of SWCNTs in the presence of lipids have been prepared, whereas their electrophoretic mobility was confirmed by ζ-potential measurements. Raman measurements revealed that smaller diameter SWCNTs are preferentially dispersed by lipid molecules in the aqueous supernatant part of the prepared suspension.